2022
DOI: 10.1021/acsomega.2c04936
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Ternary NLP/ZnO@l-cysteine-grafted-PANI Bionanocomposites for the Selective Removal of Anionic and Cationic Dyes from Synthetic and Real Water Samples

Abstract: The development of competent adsorbents based on agro-waste materials with multifunctional groups and porosity for the removal of toxic dyes from aqueous solutions is still a challenge. Herein, a bionanocomposite made up of neem leaf powder (NLP), zinc oxide (ZnO), and amino acid (L-cysteine)-functionalized polyaniline (PANI), namely, NLP/

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 66 publications
0
0
0
Order By: Relevance
“…In Fig. 3b, HR-FESEM visibly demonstrated that rough, porous, and surface of adsorbent has been filled by adsorption 1 of BG and CR dyes. After dyes adsorption…”
Section: High Resolution Field Emission Scanning Electron Microscopy(...mentioning
confidence: 97%
See 1 more Smart Citation
“…In Fig. 3b, HR-FESEM visibly demonstrated that rough, porous, and surface of adsorbent has been filled by adsorption 1 of BG and CR dyes. After dyes adsorption…”
Section: High Resolution Field Emission Scanning Electron Microscopy(...mentioning
confidence: 97%
“…Hence different colouring effluents cannot be liquidated without suitable treatment in the water bodies. Due to their complex orientation and synthetics routes 1 , these colouring organic effluents cannot be effortlessly removed or degraded with effluents removing methods. Such dyes are designed to resist disintegration in required amount of time.…”
Section: Introductionmentioning
confidence: 99%